Identifikasi Kecanduan Gadget Pada Anak dengan Menerapkan Metode Fuzzy Logic Sugeno - Virdyra Tasril; Ade Rizka; Munisa Munisa; Siti Dewi Murni (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The development of technology 4.0 is increasingly advanced, followed by the development of children's learning methods in the world of education. Since the covid pandemic, children are required to study from home with the help of technology in the form of using mobile phones, tablets, or computers and laptops as a medium of communication in learning. Children in the Alpha generation have started using gadgets in education. As a result of using gadget media every day, children are happy to play games and also see youtube applications. The purpose of this study was to identify how high gadget addiction is in children. Gadget addiction often impacts social behavior and affects the eating patterns of children with a reasonably high gadget addiction. The data analysis method used in this study uses Fuzzy Sugeno analysis with the help of Matlab software. The population of this study was parents and seventh-grade elementary school children who often used gadgets. Data were obtained by distributing questionnaires, conducting interviews, and documenting.